Gender and growth in Sub-Saharan Africa: Issues and evidence - Mark Blackden; Sudharshan Canagarajah; Stephan Klasen; David Lawson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The study suggests that gender inequality acts as a significant constraint to growth in sub-Saharan Africa, and that removing gender-based barriers to growth will make a substantial contribution to realizing Africa's economic potential. In particular we highlight gender gaps in education, related high fertility levels, gender gaps in formal sector employment, and gender gaps in access to assets and inputs in agricultural production as particular barriers reducing the ability of women to contribute to economic growth. By identifying some of the key factors that determine the ways in which men and women contribute to, and benefit (or lose) from, growth in Africa, we argue that looking at such issues through a gender lens is an essential step in identifying how policy can be shaped in a way that is explicitly gender-inclusive and beneficial to growth and the poor. We also argue that in some dimensions and channels of the gender-growth nexus, the evidence is only suggestive and needs further detailed research and analysis. Investigations of the linkage between gender inequality and growth should therefore be a priority for development economics research in coming years. – gender ; growth ; sub-Saharan Africa
Keywords: O4; J16; J2; 330; Wirtschaftswachstum; Zentralafrika; Gleichberechtigung